Development of adaptive thermal comfort model for urban park based on field survey and literature review - Subedi, Rupendra; Rijal, Hom B.; Khadka, Supriya; Aqilah, Naja; Lamsal, Prativa (Frontiers in Built Environment, 2025)
Global warming has caused an increase in extreme heatwaves. Research on outdoor thermal comfort in urban parks has been carried out in different countries under various climatic conditions. However, there is lack of information on outdoor thermal comfort in Nepal. The main objectives of this study are to show the thermal sensations of park visitors, estimate the comfort temperature, compare the results of thermal indices with those from previous studies, and develop an adaptive thermal comfort model for the outdoor environment based on a thermal comfort survey and literature review. The study was conducted using digital instruments, and we gathered a total of 147 responses. The results showed that 78% and 81% of visitors voted in favor of “4. Neutral” thermal sensations during summer and autumn, respectively, indicating that they were highly satisfied with the thermal environment of the park. Linear regression analysis was used to estimate the comfortable physiological equivalent temperature (PET) and comfortable universal thermal climate index (UTCI) of the park, which were determined as 30.0°C and 28.5°C, respectively. These indices are correlated with the outdoor temperature, so an adaptive thermal comfort model was proposed based on literature review. The results obtained from the field survey were validated through extensive literature review. The comfortable PET, comfortable UTCI, and adaptive model were compared with several studies from different parts of the world reported to have various climatic conditions. We expect that landscape architects and urban planners can use these models to maximize outdoor thermal comfort and create more comfortable as well as healthy living environments for city dwellers.